Implementasi Kurikulum Merdeka Belajar di Sekolah Penggerak - Novrita Suryani; Mohamad Muspawi; Aprillitzavivayarti Aprillitzavivayarti (Universitas Batanghari Jambi, 2023)
This study aims to analyze the implementation of the Independent Learning Curriculum in driving and inhibiting schools. This study uses a qualitative approach, which focuses on describing an event and events that have occurred at the time the research was conducted. Collecting data using observation techniques, interviews and documentation. To analyze the data used data management, coding and making themes, and presenting the results of processed data. The research results show that in implementing the independent curriculum in driving schools, starting with planning which consists of compiling the Education Unit Operational Curriculum, making teaching modules, then the implementation stage begins with intracurricular learning, and learning through projects to strengthen the Pancasila student profile, and finally from implementing the independent curriculum namely evaluation consisting of assessment, grade promotion criteria, and graduation criteria. there are obstacles to the implementation of the independent curriculum in driving schools namely the lack of references where the books prepared are incomplete and not in accordance with the independent learning ceiling, the lack of experience of teaching staff (teachers) and there are still teachers who have not changed in accepting technology-related updates